Fuzzy C-Means Algorithm Based Satellite Image Segmentation - Syed Nazeebur rehman; Mohameed Ali Hussain (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
In this paper, an improved version of Fuzzy C-Means (FCM) algorithm is proposed efficiently to segment the satellite images. Segmentation of Image is one of the promising and active researches in recent years. As literature prove that region segmentation will produce better results. Human visual perception is more effective than any machine vision systems for extracting semantic information from image. A FCM algorithm is developed to estimate parameters of the prior probabilities and likelihood probabilities. So FCM algorithm is used for segmenting background and island extraction is done based on pixel intensity. Finally Peak Signal to Noise Ratio (PSNR) is calculated and it has better results than other.